2021
DOI: 10.2217/cer-2020-0224
|View full text |Cite
|
Sign up to set email alerts
|

Cost–effectiveness of an insertable cardiac monitor to detect atrial fibrillation in patients with cryptogenic stroke

Abstract: Background: We assessed cost–effectiveness of insertable cardiac monitors (ICMs) in a US cryptogenic stroke population. Materials & methods: We modelled lifetime costs and quality-adjusted life years for three monitoring strategies post cryptogenic stroke: ICM starting immediately, ICM starting after Holter monitoring (delayed ICM) and standard of care involving intermittent ECG and Holter monitoring. Patient characteristics and detection efficacy were based on the CRYSTAL-AF trial. AF detection altered th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Finally, although our observations indicate that some stroke care pathways include a trial of ECMs before ICM (likely due in part to the higher upfront cost of the ICM device), recent cost-effectiveness analysis found this approach to be overall on average cost-additive compared to use of an ICM directly after CS, due to the low likelihood of diagnosis with an initial ECM. 21 These considerations may be important in jurisdictions with constrained health care resources, in which short- vs long-term clinical and economic implications must be weighed. Further research should focus on assessing economic and clinical implications of stroke monitoring pathways outside the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although our observations indicate that some stroke care pathways include a trial of ECMs before ICM (likely due in part to the higher upfront cost of the ICM device), recent cost-effectiveness analysis found this approach to be overall on average cost-additive compared to use of an ICM directly after CS, due to the low likelihood of diagnosis with an initial ECM. 21 These considerations may be important in jurisdictions with constrained health care resources, in which short- vs long-term clinical and economic implications must be weighed. Further research should focus on assessing economic and clinical implications of stroke monitoring pathways outside the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have examined the cost-effectiveness of ILR but have used a time horizon of over a lifetime, 24,[33][34][35] which is not relevant to our one-year timeframe. No prior modeling study has examined the costs of MCOT from the US perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Values were derived from published studies identified through targeted literature review. All-cause mortality rates were derived from Sawyer et al 33 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations